Desisters in the making? Exploring the capacity to desist during community transition among a small longitudinal panel of releasees. Issue 1 (1st January 2018) - Grommon, Eric; Rydberg, Jason
Abstract: Self-narratives signal readiness for change and the capacity to desist from crime. Utilizing longitudinal interviews with 39 male subjects in a small, industrialized, Midwestern US city, this study explores self-narratives to gain additional understanding about desistance and the malleable components that shape the process. In contrast to existing long-term desistance studies, this research considers the presence of desistance-promoting narratives during reentry. Data on three waves of interviews conducted shortly after release and three or more months after the first interview are presented. Results indicate that returning prisoners engage with desistance-promoting themes during the immediate reentry process, and that the prevalence and importance of these themes change with additional time in the community. The implications of these findings for reentry policy, practice, and research are discussed.